COMMUNICATION WITH SUPERNATURAL PROTECTORS AND HELPERS IN ESTONIA IN THE 21ST CENTURY (Religious dialogue and cooperation, 2025)
Estonia has been repeatedly called the least religious country in Europe or even thewhole world. The Estonian mainstream media and politics mainly resonate with the identificationof Estonians as a rational high-tech and science-oriented nation. Although the number of peoplewho believe in biblical God and/or feel affiliated to any canonical religion is indeed low accordingto representative polls, there are numerous other forms for communicating with the numinous(e.g., in the form of protective angels, spirit animals, nature spirits, spirits of dead relatives, or petswho give spiritual guidance) observable in the Estonian society. Based on personal experience narrativesfrom the recent decade, this article will give an overview of supernatural helpers and protectorswith whom people in Estonia communicate. Answers will be sought to the following questions:Who are these beings? From which traditions do they stem? Which ways of communicatingwith them are practiced? What are the differences compared to older layers of religion? This paperwill demonstrate a recent heterogenous pluralism, presented in the co-existence and fluctuationof – partly situational – beliefs in various supernatural figures, and try to locate these findings inthe current (post)secularization debates. The author concludes that such contemporary models ofreligious beliefs and practices are not necessarily replacing the traditional ones but rather recyclealready existing religious ideas in somewhat modified configurations that are adjusted to the contemporaryneeds. Despite the rather polarized view of religion and science in the mainstream mediaand political discourse, the empirical material shows that such vernacular beliefs and practicesmay build symbioses with scientific conceptions of the world.
Keywords: supernatural protectors; communication with the numinous; contemporary spirituality; belief narratives